2020
DOI: 10.1002/jbt.22553
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic coumarin derivative (4‐flourophenylacetamide‐acetyl coumarin) impedes cell cycle at G0/G1 stage, induces apoptosis, and inhibits metastasis via ROS‐mediated p53 and AKT signaling pathways in A549 cells

Abstract: New chemotherapeutic agents with minimum side effects are indispensable to treat non-small-cell lung cancer (NSCLC) since the mortality rate of patients suffering from NSCLC remains high despite receiving conventional medication. In our previous study, many coumarin derivatives were screened for their anticancer properties in A549, an in vitro NSCLC model. One of these, 4-flourophenylacetamideacetyl coumarin (4-FPAC), induced cytotoxicity at a concentration as low as 0.16 nM. Herein, initially, the cytotoxic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…5 Recent studies have shown that the activation of PI3K/AKT signaling pathway can modulate proliferation, apoptosis, cycle arrest, migration and invasion of lung cancer cells. 6,7 Phosphatase and tensin homologue deleted on chromosome ten (PTEN), a lipid phosphatase that functions as a tumor suppressor, has been widely affirmed to suppress tumor progression through PI3K/AKT signaling pathway. 8 MicroRNAs (miRNAs) are endogenous non-coding small RNA molecules, which mediate the gene expression at the post-transcriptional level by binding to mRNAs, thus participating in the regulation of various biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent studies have shown that the activation of PI3K/AKT signaling pathway can modulate proliferation, apoptosis, cycle arrest, migration and invasion of lung cancer cells. 6,7 Phosphatase and tensin homologue deleted on chromosome ten (PTEN), a lipid phosphatase that functions as a tumor suppressor, has been widely affirmed to suppress tumor progression through PI3K/AKT signaling pathway. 8 MicroRNAs (miRNAs) are endogenous non-coding small RNA molecules, which mediate the gene expression at the post-transcriptional level by binding to mRNAs, thus participating in the regulation of various biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Anticancer properties of various coumarin derivatives were comprehensively examined and it is clear that they can inhibit the growth, proliferation, and metastasis of cancer cells (Figure 1). [ 18–30 ]…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence showed that phosphoinositide kinases played a momentous role in mediating viral infections ( Burke, 2018 ), and the coumarin derivatives exhibited a tremendous inhibitory activity toward the phosphoinositide 3-kinase (PI3K) and protein kinase B (Akt) pathways ( Ma and Liu, 2017 ; Umar et al, 2020 ). We also explored the possible role of N6 targeting the PI3K/Akt signaling pathway during HTNV infection.…”
Section: Resultsmentioning
confidence: 99%